EFFORTS TO INCREASE INTEREST AND LEARNING OUTCOMES OF ECONOMIC SUBJECTS THROUGH ACTIVE DEBATE METHOD - Wardana, Ribut Wardana (Journal of Education Technology and Inovation, 2022)
Learning becomes quality if students can be actively involved in creating a meaningful learning process. The results of initial observations in class XII Social Sciences 3 SMA Negeri 1 Tanggul Even Semester for the 2019/2020 Academic Year obtained data on the Economics subject teaching material "Characteristics of Trading Companies " students who have not achieved completeness as much as 44%, meaning that most students have not been actively involved in learning . The subjects and at the same time the objects in this study were all 36 students of class XII IPS 3 as many as 36 students. This research is a type of quantitative research. Data collection by the questionnaire method. The data analysis technique used is statistical analysis. In this Classroom Action Research, the researcher wants to provide a learning method that has never been applied before, namely the active debate method in Economics in class XII IPS 3 SMA Negeri 1 Tanggul Even Semester for the 2019/2020 Academic Year. Students of class XII IPS 3 were chosen as subjects in the study, because researchers wanted to improve learning outcomes which so far have not been as expected.Active debate is a form of terrorism or argument, either orally or in writing, between two people or groups of different opinions, by attacking or influencing each other so that they want to carry out, act, follow or at least have a tendency in accordance with what is desired by the speaker or writer